Web-Based Health Services in Forensic Psychiatry: A Review of the Use of the Internet in the Treatment of Child Sexual Abusers and Child Sexual Exploitation Material Offenders - Wild, Tamara S. N.; Fromberger, Peter; Jordan, Kirsten; Müller, Isabel; Müller, Jürgen L. (Frontiers in Psychiatry, 2019)
In recent years, web-based health services for a variety of mental disorders have been developed and evaluated. Evidence suggests that guided internet-based therapy can be as effective as conventional face-to-face therapy. In forensic psychiatric practice, few web-based treatments have been implemented up to now. However, to our knowledge, there do not yet exist guided internet-based treatments for child sexual abusers and child sexual exploitation material offenders. This review aims at examining under what conditions patients are most likely to benefit from internet-based treatments. In addition, some computer-based health services in forensic psychiatry will be summarized and their potentials and weaknesses will be discussed. Subsequently, the review focuses on the implications for the development of online treatments for child sexual abusers as well as on a variety of ethical and legal issues that practitioners may encounter during the development, evaluation and delivery of online health services. The review will conclude with proposed quality standards for the development and implementation of web-based interventions for child sexual abusers and child sexual exploitation material offenders. By virtue of the low number of psychotherapists offering therapy to this clientele as well as individual barriers to seeking treatment, the development of mental eHealth services in this sector could close an important healthcare gap. By increasing the density of supply, more child sexual abusers and child sexual exploitation material offenders would have the chance to engage in treatment and, ultimately, more incidents of sexual assault against minors could be prevented.